Studio anywhere : a photographer's guide to shooting in unconventional locations - Fancher, Nick (Peachpit Press, 2015)
What's your definition of a photo studio? Is it a room with a white seamless backdrop or a cyc wall? Maybe it's simply anywhere you're in control of the lighting. In a perfect world, where every day is a breezy 72 degrees with partial cloud coverage, we would all have a 5,000-square-foot studio - and the entire catalog of B&H in our equipment lockups. But the reality is that you may have an outdated DSLR with two decent lenses (which took you several years to save up for), and all you have at your disposal is an unfinished basement, your garage, or the empty conference room at your office. That's where Studio Anywhere comes in. With photographer Nick Fancher as your guide, you'll learn how to get portfolio-ready photos while working in some of the most problematic scenarios imaginable. Whether shooting a corporate portrait, a test shoot with a model, or a promo shoot with a band, you'll discover that most of the time, there's no need for an expensive studio - you just have to get creative. Studio Anywhere is a resource for photographers to learn through behind-the-scenes photos and lighting diagrams from a range of photo shoots - but it doesn't stop there. Because directing a photo shoot involves more than simply knowing how to wield a camera or process a raw file, Nick also lets you in on the aesthetic decisions he makes in his signature photos, inspiring you to develop your own vision. And, finally, he describes his Lightroom and Photoshop workflow so you can learn how to deftly navigate post-processing. Shows how to create images with minimal equipment that is within reach of anyone's budget Takes you through the entire shoot, from concept to lighting to exposure to post-processing in Lightroom and Photoshop Teaches how to build a portfolio without a dedicated studio space.